Capillary Rise in Layered Soils - Zhenhua Zhao; Zhenjiang Luo; Hongjie Sun; Haitao Li; Qiang Liu; Haiyan Liu (Applied Sciences, 2023)
Capillary rise tests were conducted on soil columns containing of three layers of sandy soils with coarser over finer over coarser sandy soil to investigate the effect of the relatively finer soil interlayer. The capillary rise height, rate, and water distribution were observed in laboratory tests of four layered soil columns, with two homogeneous (without the interlayer) soil columns serving as the controls. The final maximum height of the capillary rise in the soil column with the interlayer was larger than that of the column without the interlayer when the interlayer was laid around the water entry value of the underlying soil. The water content was not continuous in the entire soil profile with the interlayer, and a small matric suction gap was observed in the relatively fine soil between the soil column with and without the interlayer.